Religious Diversity, APC 2023 Same Faith Presidential Ticket and Social Cohesion in Nigeria - Yusuf, Danjuma; Abraham, Agan; Dankano, Edwe; Jev, Amos (Kashere Journal of Politics and International Relations, 2025)
Nigeria is a pluralistic and multicultural society with people of diverse ethnic origins and different religions. The nation grapples with social upheavals that have threatened it existence. Religious divide in the country has also been seen to cause political tensions between Christians and Muslims in the country. Using secondary method of data collection, the paper found that, though during the 1993 presidential election, SDP presidential candidate and the running mate were both Muslims but, since the beginning of the fourth republic in 1999, the major political parties have been careful in the nomination of their presidential candidates and running mates coming from the same faith, given the polarization of religion in the country. However, during the 2023 presidential election, the ruling All Progressive Congress presented Ahmed Bola Tinubu a Muslim from the south and Kashim Shettima a Muslim from the north. This arrangement sparked lots of agitations among the Christian APC members and the Christian community in the country at large. Though the ruling APC disclosed that it was not an intentional act to demean the Christian population in the country but a strategy towards winning the election. This implication equally reflected on the pattern of vote. It was found that, some states that were controlled by APC governors with dominant Christians, voted for other political parties with mix ticket than APC hence, the citizens are more divided on the basis of religion than ever before.